The Level of Competencies of Postgraduate Students in Using the "Google Scholar" Platform from Their Viewpoint (A Field Study at the Faculty of Education at Tishreen University) - اللوحة, محمد; مطيعة أحمد; يوسف شاهين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aims to determine the level of competencies using the "Google Scholar" platform from the viewpoint of a sample of postgraduate students at the Faculty of Education at Tishreen University, in light of the two variables: academic degree and scientific department. To achieve the research objectives, a descriptive approach was used, and a competencies questionnaire was prepared and distributed to a simple random sample of (135) postgraduate students. The data was collected and statistically analyzed, and the researcher arrived at the following results: The level of competencies of postgraduate students in using the "Google Scholar" platform is generally low. The academic degree does not affect the competencies level of postgraduate students in using the Google Scholar platform.. The scientific department does not affect the competencies level of postgraduate students in using the Google Scholar platform. The research ended with a set of recommendations, such as: provision of regular supportive workshops to assist students in effectively using the Google Scholar platform and fully benefiting from its features. It also suggests the establishment of a personal profile in the Google Scholar platform and the addition of published research as prerequisite for master's and doctoral students in all departments of the Faculty of Education, ensuring that the university thesis is not discussed without achieving this requirement.